Realising poverty in all its dimensions: A six-country participatory study. (October 2020) - Bray, Rachel; de Laat, Marianne; Godinot, Xavier; Ugarte, Alberto; Walker, Robert
Highlights: People experiencing poverty, welfare workers and academics agree on the dimensions of poverty. Only three of the nine recognised dimensions of poverty are regularly measured. It is now possible to discuss and address poverty in the global North and South based a single conceptualisation. The nine dimensions of poverty provide a template for developing and evaluating anti-poverty programmes. Abstract: The Sustainable Development Goals require countries to halve poverty in all its dimensions by 2020 but the dimensions are nowhere specified. Reflecting the United Nation's aspiration that policy should be informed by 'the meaningful participation of persons living in poverty', participative research was undertaken in six contrasting countries (Bangladesh, Bolivia, France, Tanzania, the United Kingdom and the USA) to identify the dimensions of poverty. People experiencing poverty were involved at all stages of the research as members of national research teams alongside academics and practitioners. The core methodology, Merging of Knowledge, entailed recruitment in each country of people in poverty, social welfare practitioners and specialist academics, their participation in extended parallel groupwork in order to specify the dimensions of poverty, and meetings between representatives of all three groups to seek consensus. Consensus was achieved at national level as it subsequently was at international level with representatives from all six countries. Nine dimensions of poverty were recognised, only three of which are commonly included in existing measures: disempowerment; suffering in body, mind and heart; struggle and resistance; social maltreatment;, institutional maltreatment; unrecognised contribution; lack of decent work; insufficient income; and material and social deprivation. Five factors were determined to influence the manifestation of the dimensions: cultural beliefs; identity; location; environment and environmental policy and timing and duration. The research suggests that it may be possible to view poverty in the global North and South through a single perspective creating a template for the development and evaluation of policy, while also stimulating work on new indicators of poverty.